Product quality and provide food to the regions of Kazakhstan: problems and opportunities - N. Zh. Brimbetova; G. K. Temirova; A. A. Sultanaev (Экономика: стратегия и практика, 2020)
Food security is part of the national security of the country, because no country can ensure national security, including economic security, without meeting the demand for quality food. Consumption of basic foodstuffs is one of the main components of the living standards of the population, a general description of the social situation in the region, the sum of the vital benefits consumed mainly by the population, as well as a key factor of stability. The study presents the results of the consumption of certain types of agricultural products per capita. The normative rights of food consumption were compared with the physiological norms of consumption, and the regional aspect of per capita consumption in terms of minimum and maximum consumption was considered. The volume of food consumption for 2015-2019 was determined, showing the leading and least consumed regions. In recent years, the level of the structure of food consumption of the population has changed significantly, which is influenced by a number of factors: national characteristics of nutrition; climate of the territory; economic factors.